2019
DOI: 10.3389/fneur.2019.01275
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Primary (Migraine) Headaches—Friend or Foe?

Abstract: Background: The actions of caffeine as an antagonist of adenosine receptors have been extensively studied, and there is no doubt that both daily and sporadic dietary consumption of caffeine has substantial biological effects on the nervous system. Caffeine influences headaches, the migraine syndrome in particular, but how is unclear.Materials and Methods: This is a narrative review based on selected articles from an extensive literature search. The aim of this study is to elucidate and discuss how caffeine may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 177 publications
(233 reference statements)
2
35
0
1
Order By: Relevance
“…As suggested by Spencer (38), caffeine withdrawal in migraineurs may serve as a human model for studying migraine. Why withdrawal could act as a trigger is unknown, but it is probably a consequence of an up-regulation of adenosine receptors during regular caffeine intake (4). Increased sensitivity to adenosine after withdrawal may increase excitability in networks involved in migraine pathophysiology, lowering the threshold for attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by Spencer (38), caffeine withdrawal in migraineurs may serve as a human model for studying migraine. Why withdrawal could act as a trigger is unknown, but it is probably a consequence of an up-regulation of adenosine receptors during regular caffeine intake (4). Increased sensitivity to adenosine after withdrawal may increase excitability in networks involved in migraine pathophysiology, lowering the threshold for attacks.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adults, cessation of daily doses of as little as 100 mg of caffeine, the equivalent of one cup of coffee, may cause a withdrawal syndrome consisting of headaches, lethargy, and other symptoms (3). Curiously, this syndrome mimics the prodromal phase of migraine, and this seems to have been overlooked when the symptoms of caffeine withdrawal have been investigated (4). Studies explicitly documenting caffeine withdrawal as a trigger for migraine seem to be lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, subcortical and lacunar infarctions are the least associated with acute headache compared to cortical strokes 16,17 . Previous studies have reported that vessels in the posterior circulation are more richly innervated by nociceptive afferents than in the anterior circulation 17‐20 . Pain signals from the circle of Willis are transmitted through the trigeminal nerve, whereas vasculature structures of the posterior fossa are innervated by the cervical plexus, vagus, and trigeminal nerve 18,20,21 .…”
Section: Headache Attributed To Cranial or Cervical Vascular Disordermentioning
confidence: 99%
“…Previous studies have reported that vessels in the posterior circulation are more richly innervated by nociceptive afferents than in the anterior circulation 17‐20 . Pain signals from the circle of Willis are transmitted through the trigeminal nerve, whereas vasculature structures of the posterior fossa are innervated by the cervical plexus, vagus, and trigeminal nerve 18,20,21 . Although incompletely understood, the pathophysiology of the headache is presumed to be related to the stimulation of the trigeminovascular afferent system, resulting in the release of vasoactive neuropeptides which mediate subsequent vasodilation 18,20 .…”
Section: Headache Attributed To Cranial or Cervical Vascular Disordermentioning
confidence: 99%
“…This type of primary headache usually presents with recurrent, typically unilateral and pulsating attacks of severe headaches, lasting from 4 to 72 h, with accompanying symptoms including photophobia, phonophobia, nausea, and vomiting [ 3 ]. Caffeine has been linked with migraine for many years, on the one hand as a trigger, and on the other as a cure [ 4 , 5 , 6 , 7 , 8 ]. As most of the population, including migraine sufferers, consume a considerable amount of coffee and other caffeinated drinks and foods daily, a question arises as to whether it influences their headaches.…”
Section: Introductionmentioning
confidence: 99%